Mediatising politics and Australian Indigenous recognition: a critical analysis of two landmark speeches - Johnston, Jane; Forde, Susan (Communication Research and Practice, 2017)
This article examines the way in which Australian political discourse and the mediatisation process has contributed to the communication of Indigenous recognition in Australia. In particular, it draws upon two key Prime Ministerial speeches from the past 25 years which dealt specifically with issues of colonisation and maltreatment of Australia’s First Nations peoples. We use Strömbäck’s four phases of mediatisation as a conceptual framework. The first speech is then Prime Minister Paul Keating’s 1992 ‘Redfern Park’ address in which he descriptively acknowledges the invasion of the land by white settlers and its impact on Indigenous peoples; the second, the 2008 ‘Apology’ speech of then newly elected Prime Minister Kevin Rudd in which he apologised to the country’s ‘Stolen Generations’ of First Nations’ people for previous government policies which removed Indigenous children from their families and placed them into white care. These speeches represent significant moments in Australian history and will be examined as case studies, cast within the developing theory of mediatisation. It is our proposition that the two speeches are situated at different entry points of the four-phased continuum of mediatisation and, as such, provide illustrations of the theory in action. Further, these case studies provide an original lens to examine the communication of Indigenous maltreatment and disadvantage – through the ways in which two Australian Prime Ministers presented these issues, through the media, to the Australian public. No Full Text